Sustaining the Productivity of Casuarina equisetifolia by Dual Inoculation with Frankia and VAM - Ravichandran, V. K.; Balasubramanian, T. N. (Indian Forester, 2006)
Casuarina equisetifolia is highly suitable for coastal wasteland afforestation. Planting of superior elite seedling plays an important role in successful afforestation. The tripartite association involving effective Frankia strain, efficient VAM and Casuarina seedling was established under pot culture condition. The results of the pot experiment revealed that 57 per cent increased drymatter accumulation per plant and enhanced nitrogen and phosphorus uptake of 205 and 177 per cent respectively due to dual inoculated seedling at 105 DAI was noticed over uninoculated control.